2014
DOI: 10.1186/s12967-014-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of recurrent BRAFV600E mutated ganglioglioma to Vemurafenib as single agent

Abstract: BackgroundGanglioglioma (GG) and pilocytic astrocytoma (PA) represent the most frequent low-grade gliomas (LGG) occurring in paediatric age. LGGs not amenable of complete resection (CR) represent a challenging subgroup where traditional treatments often fail. Activation of the MAP Kinase (MAPK) pathway caused by the BRAFV600E mutation or the KIAA1549-BRAF fusion has been reported in pediatric GG and PA, respectively.Case presentationWe report on a case of BRAFV600E mutated cervicomedullary GG treated with stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 38 publications
4
45
2
1
Order By: Relevance
“…In contrast, we document successful sustained objective response and re‐response to single agent vemurafenib for 1 year and for 9 months and ongoing, respectively. Similar to our report, an infant with recurrent cervicomedullary GG was treated with vemurafenib as a single agent and demonstrated a sustained response at a follow up of only 6 months . The responses of two additional patients with anaplastic GGs treated with vemurafenib also have been reported .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, we document successful sustained objective response and re‐response to single agent vemurafenib for 1 year and for 9 months and ongoing, respectively. Similar to our report, an infant with recurrent cervicomedullary GG was treated with vemurafenib as a single agent and demonstrated a sustained response at a follow up of only 6 months . The responses of two additional patients with anaplastic GGs treated with vemurafenib also have been reported .…”
Section: Discussionsupporting
confidence: 86%
“…BRAF inhibitors offer an alternative treatment approach for refractory BRAFV600E positive (+) BS GGs. Although there are two previous case reports of objective tumor response to Vemurafenib in pediatric BRAFV600E (+) BS GG, only one utilized vemurafenib as a single agent, and the reported follow‐up time on treatment in each case was short (3–6 months) . In pediatric BS GG, information regarding the potential duration of response and clinical course during and after the discontinuation of long‐term administration of vemurafenib is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There are now several BRAFV600E specific inhibitors in clinic and individual case reports are encouraging regarding the clinical activity in BRAFV600 mutated gliomas (15)(16)(17). The PNOC is currently conducting a phase I clinical trial of specific BRAFV600E inhibitor vemurafenib in children with BRAFV600E mutated gliomas.…”
Section: Brafv600 Inhibitionmentioning
confidence: 99%
“…Pilocytic astrocytomas exhibiting genetic abnormalities disrupting MAPK are candidate diseases for these molecular targeted therapies. Interestingly, it has been shown that pilomyxoid astrocytoma, ganglioglioma and pleomorphic xanthoastrocytoma, which are other subtypes of gliomas with frequent MAPK signaling pathway activation, can respond to vemurafenib [45][46][47].…”
Section: Grade I Gliomamentioning
confidence: 99%